Magnetism in organic radical ion salts and complexes based on nitronyl nitroxide - Sugano, T; Blundell, S; Hayes, W; Day, P (2001)
Magnetic properties of purely organic radical ion salts and complexes based on nitronyl nitroxide (NN) derivatives were investigated. The salts and complexes are composed of N-alkylareniumyl NN as the radical cations and carboxylatoaryl, sulfonatoaryl and imidazolidyl NN as the radical anions. Tetracyanoquinodimethanide (TCNQ)(-) salts and complexes were also prepared. The results obtained for several complexes of a multifunctional molecule, 2-imidazoly NN (2-IMNN), are presented in detail, because 2-IMNN can be converted to various with p-carboxylatophenyl NN states by electron and proton transfers. The proton-transfer complex of 2-imidazoliniumyl NN (2-IMNN)(+*) with (p-CAPNN)(-*) shows magnetic behavior relevant to coexistence of intermolecular ferro- and antiferro-magnetic interactions. Several quinoliniumyl NN(QNNN)(+*)(p-CAPNN)(-*) complexes exhibit magnetic behavior similar to that observed in (2-IMNN)(+*)(p-CAPNN)(-*).